Phase Diagram of Nickelate Superconductors Calculated by Dynamical Vertex Approximation - Held, Karsten; Si, Liang; Worm, Paul; Janson, Oleg; Arita, Ryotaro; Zhong, Zhicheng; Tomczak, Jan M.; Kitatani, Motoharu (Frontiers in Physics, 2022)
We review the electronic structure of nickelate superconductors with and without effects of electronic correlations. As a minimal model we identify the one-band Hubbard model for the Ni 3d x 2 −y 2 orbital plus a pocket around the A-momentum. The latter however merely acts as a decoupled electron reservoir. This reservoir makes a careful translation from nominal Sr- doping to the doping of the one-band Hubbard model mandatory. Our dynamical mean-field theory calculations, in part already supported by experiment, indicate that the Γ pocket, Nd 4f orbitals, oxygen 2p and the other Ni 3d orbitals are not relevant in the superconducting doping regime. The physics is completely different if topotactic hydrogen is present or the oxygen reduction is incomplete. Then, a two-band physics hosted by the Ni 3d x 2 −y 2 and 3d 3z 2 −r 2 orbitals emerges. Based on our minimal modeling we calculated the superconducting T c vs. Sr-doping x phase diagram prior to experiment using the dynamical vertex approximation. For such a notoriously difficult to determine quantity as T c , the agreement with experiment is astonishingly good. The prediction that T c is enhanced with pressure or compressive strain, has been confirmed experimentally as well. This supports that the one-band Hubbard model plus an electron reservoir is the appropriate minimal model.